Measuring Validity and Reliability of the Model of Islamic Religious-Personality and Social Environment as a Mediator - Nuriman, Nuriman; Ibrahim, Syahrial Razali (SCAD Independent, 2020)
This study aims to measure the validity and reliability of the Islamic Religious-Personality and Social Environmental (IRPS) model. Religiosity and spirituality mediated by social environment variables were measured by SEM-PLS. Cognitive development by Piaget and the spiritual development theory by Fawler were applied in this study. The quantitative approach as a data analysis tool for the five hypotheses developed in the model. To ensure the validity and reliability of the converger validity instrument, Deverger validity and Construct Reliability test were involved with 32 items, and indicators that were valid and reliable were used to measure the Religiosity and Spirituality mediated by the social environment towards the personality of the adolescent. A total of 381 samples had been taken with systematic random sampling. The sample consisted of high school students, vocational schools, and Islamic senior high schools. The age of the respondents consisted of 16-19 years consists of 112 males and 169 females. The IRPS model that was developed has gone through a predictive relevance test and it turns out that it can be used to measure Islamic Religion-Personality through a Social Environment. The study found that there was an influence of Islamic religiosity on adolescent personality and adolescent personality not influenced by Islamic spirituality. Islamic religiosity and spirituality correlated with the social environment and positively influencing the personality of adolescents.